Academic Achievement Gap in Different Mathematical Skills/Abilities of Grade V Students - Giri, Chandra Kanta; Gowramma I.P. (INDIAN EDUCATIONAL REVIEW, 2021)
The aim of the study was to find out the academic achievement gap of Grade V students in different mathematical skills/abilities. Academic achievement gap refers to the gap or difference between academic achievement that should be expected from the students according to their grade position and the academic achievement which is found in their performance based on a mathematical test administered in the study. Different mathematical skills/ abilities considered for this study were number concept, addition, subtraction, multiplication, division, geometry, measurement, time, calendar, money and pattern. This study was a part of an experimental research and Grade V students of a school (chosen purposively) were the participants of the study. To find academic achievement gap in different mathematical skills/abilities a test on mathematical skills/abilities was administered. It was found that all the participants have academic achievement gap in measurement and calendar; 96 per cent participants in number concept and multiplication; more than 80 per cent in rest of the mathematical skills/abilities. Surprisingly it was seen that more than 70 per cent of the total participants have not reached Grade I level in 5 mathematical skills/abilities out of the 11 skills/abilities that are assessed. Due to this academic achievement gap, students struggled to learn mathematics as they go to higher grades. Hence, there is a need to identify this in the initial stage of school education and bridge the gap as early as possible.